Mechanism of Astragaloside-Brucea javanica oil nanoemulsion against oral squamous cell carcinoma through CDK1/MTFR2: Network pharmacology, bioinformatics, and experimental studies - Yihan Lai; Runqiang Liu; Huajie Shao; Juan Zhan; Yujie Ma; Lanfei Zhou; Zhichao Wan; Sicheng Li; Wei Wang; Lin Jiang; Yisen Shao (PLoS ONE, 2025)
Objective This study aims to investigate the core target of Astragaloside-Brucea javanica oil nanoemulsion (AS/BJO-NEs) against oral squamous cell carcinoma (OSCC) through network pharmacology, bioinformatics, and in vivo/in vitro experiments, elucidating its effects on epithelial-mesenchymal transition (EMT) mediated via MTFR2 and the underlying molecular mechanisms. Methods By integrating network pharmacology and weighted gene co-expression network analysis, critical gene modules linked to tumor phenotypes, EMT-related adverse prognosis, and elevated MTFR2 expression were identified, pinpointing the core target gene. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, Gene Set Enrichment Analysis, molecular docking and molecular dynamics simulation were utilized for analysis and verification. OSCC cells (SCC9 and CAL27) were cultured, and stable cell lines with CDK1 knockdown or overexpression were established. The effects of AS/BJO-NEs on cell proliferation, migration, invasion, as well as the expression levels of related genes and proteins were evaluated. In vivo, OSCC xenograft models were established in nude mice. Following treatment with AS/BJO-NEs, tumor growth inhibition and changes in the expression of relevant genes were assessed. Results CDK1 is the core target gene of AS/BJO-NEs against OSCC, and the two can bind stably. CDK1 and MTFR2 showed highly expressed in OSCC and strongly correlated with poor prognosis and EMT. In vitro experiments revealed that AS/BJO-NEs could suppress the proliferation, migration and invasion of OSCC, and down-regulate CDK1, MTFR2 and N-cadherin, whereas up-regulate E-cadherin expression. Knockdown and overexpression of CDK1 further confirmed its effects on OSCC cell phenotype, its regulatory relationship with MTFR2, and the intervention effects of AS/BJO-NEs. In vivo experiments confirmed that AS/BJO-NEs significantly inhibited tumor growth and reduced the expression of CDK1 and MTFR2 in tumor tissues. Conclusion This study demonstrated that AS/BJO-NEs inhibited the proliferation, migration, invasion and EMT process of OSCC by down-regulating CDK1 and subsequently reducing MTFR2 expression, exerting anti-tumor effects and providing new possibilities and a theoretical foundation for OSCC treatment.